Amyloid-β adopts a conserved, partially folded structure upon binding to zwitterionic lipid bilayers prior to amyloid formation. Issue 5 (10th November 2015) - Korshavn, Kyle J.; Bhunia, Anirban; Lim, Mi Hee; Ramamoorthy, Ayyalusamy
Abstract : Aggregation at the neuronal cell membrane's lipid bilayer surface is implicated in amyloid-β (Aβ) toxicity associated with Alzheimer's disease; however, structural and mechanistic insights into the process remain scarce. Abstract : Aggregation at the neuronal cell membrane's lipid bilayer surface is implicated in amyloid-β (Aβ) toxicity associated with Alzheimer's disease; however, structural and mechanistic insights into the process remain scarce. We have identified a conserved binding mode of Aβ40 on lipid bilayer surfaces with a conserved helix containing the self-recognition site (K16-E22).